The facilities provided for disable people and elderly persons in ablution area at Masjid An-Nur, Universiti Teknologi Petronas / Nur Fareeda Khalid. - Khalid, Nur Fareeda (2014)
Solat is the second pillars in Islam. To perform solat, ones have to perform the ritual ablution or wudu. In the mosque, ablution area is provided but not all mosques considering the requirements for disabled users. The design of ablution area should ensure the comfort level of people including disabled users and also elderly person. The aim of this research is to obtain the appropriate requirements for ablution area for disabled people at Masjid An-Nur, Universiti Teknologi Petronas. This research study will identify the facilities needed for disabled users in the ablution area and the comfort level and satisfaction of the users with the provided facilities in the ablution area.